Embryologic layers in dermatology: Developmental checkpoint disorders, diagnostic insight, and regenerative futures - KAYA G.; YAZICI G. N.; ALAVANDA C.; KÜÇÜK Ö. S. (My University, 2026)
Objectives: This review aims to present a developmental framework linking embryonic lineage with non-heritable cutaneous anomalies to improve diagnostic precision and educational approaches in dermatology. Materials and Methods: A narrative literature review was conducted using PubMed, Scopus, and Web of Science databases covering the years 2000-2025. Keywords included \"skin development\" \"embryology,\" \"developmental checkpoint disorders,\" and \"non-genetic congenital disorders.\" Data on morphogenesis, embryologic signaling pathways, and representative disorders were synthesized into a layer-based model. Results: Disorders such as selfhealing collodion baby (periderm retention anomaly), pigmentary mosaicism (postzy-gotic melanocyte patterning defect), and focal dermal hypoplasia (connective tissue maldevelopment) reflect disruptions at specific morphogenetic checkpoints. Mapping these conditions to their embryonic origins revealed layer-specific vulnerability windows and facilitated differential diagnosis from inherited disorders. Understanding these embryologic principles supports earlier diagnosis, informed prenatal counseling, and structured integration into dermatology curricula. Advances in regenerative medicine, particularly stem cell-based strategies, highlight the translational potential of dermatoembryology in developing targeted therapies. Conclusion: A layer-oriented der-matoembryological perspective enhances recognition of developmental skin disorders, especially when genetic analyses are inconclusive. Incorporating embryologic concepts into clinical reasoning not only improves diagnostic accuracy but also fosters regenerative therapeutic innovations and enriches dermatology education.
Keywords: Tıp; Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Mikrobiyal Genetik; Sağlık Bilimleri; Temel Tıp Bilimleri; Anatomi; Biyokimya; Temel Bilimler; Medicine; Life Sciences; Molecular Biology and Genetics; Microbial Genetics; Health Sciences; Fundamental Medical Sciences; Human Anatomy; Biochemistry; Natural Sciences; Yaşam Bilimleri (Life); Biyoloji ve Biyokimya; Anatomi ve Morfoloji; Gelişimsel Biyoloji; Life Sciences (Life); Biology & Biochemistry; Molecular Biology & Genetics; Anatomy & Morphology; Developmental Biology; Embriyoloji; Anatomy; Embryology; congenital disorders; dermatology; embryonic development; regenerative medicine; skin abnormalities